Coaching in the process of individual and organizational development - Lange, Amanda (2014)
In the course of the last century, changes in work and in the organizational level became constant. This scenario favored the emergence of new administrative tools, among which the coaching has been receiving prominence. The organizational coaching represents a means of working with people and to make them more competent and more accomplished. The overall objective of this article is to identify and analyze the contribution of coaching for the individual and for the organization. This study characterizes itself as a qualitative research of exploratory type, whose data were collected through in-depth interviews with leaders of organizations, who participated in coaching processes. As main results, identified are the development of the ability to lead and the focus and the enhancement of communication and the interpersonal relations.